2010
DOI: 10.1007/s10103-010-0822-9
|View full text |Cite
|
Sign up to set email alerts
|

Microtensile bond strength of composite resin to glass-infiltrated alumina composite conditioned with Er,Cr:YSGG laser

Abstract: Tribochemical silica-coating is the recommended conditioning method for improving glass-infiltrated alumina composite adhesion to resin cement. High-intensity lasers have been considered as an alternative for this purpose. This study evaluated the morphological effects of Er,Cr:YSGG laser irradiation on aluminous ceramic, and verified the microtensile bond strength of composite resin to ceramic following silica coating or laser irradiation. In-Ceram Alumina ceramic blocks were polished, submitted to airborne p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…The treatments to roughen the surface include roughing with burs, acid etching with hydrofluoric or phosphoric acid, and air-borne particle abrasion [8,9]. Most recently, researchers have focused on the efficiency of lasers for composite repair bond strength [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The treatments to roughen the surface include roughing with burs, acid etching with hydrofluoric or phosphoric acid, and air-borne particle abrasion [8,9]. Most recently, researchers have focused on the efficiency of lasers for composite repair bond strength [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Today, the use of materials that are aesthetically acceptable has become more popular in restorative dentistry . Ceramics are the most aesthetic materials available in restorative dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a standard method with optimal power and strength is needed to prepare the porcelain surface for repair without any detrimental effects . Many studies on the efficacy of ceramic surface treatment using burs, etching with hydrofluoric acid (HF), phosphoric acid, accidulated phosphate fluoride, ammonium bifluoride, lasers (CO 2 , Er‐YAG, ND‐YAG, Er,Cr‐YSGG) and sandblasting have been published that reportedly increase the bond strength of resin material to porcelain …”
Section: Introductionmentioning
confidence: 99%
“…More recently, high power lasers have been investigated for potential use on ceramic conditioning. There are still few studies in the literature about laser treatment of dental ceramics; however, the results indicate that high power lasers can provide similar or even higher bond strength values than those obtained with Rocatec System when adequate irradiation parameters were used [3, 4, 43]. Despite the promising results regarding laser conditioning of high-crystalline ceramics, several studies in the literature do not report this increase in bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported their promising results when used for the treatment/irradiation of the inner surface of ceramic restorations [24], as well as for the microbial reduction at the dentin surface and subsurface [59]. On the other hand, low power lasers are used for modulation of inflammatory process, pain reduction, and soft tissue biomodulation [1017].…”
Section: Introductionmentioning
confidence: 99%